Formulation and application of clove essential oil-based nanoemulsion against Ruellia tuberosa L. - Somala, N.; Laosinwattana, C.; Dimak, J.; Teerarak, M. (My University, 2023)
Clove essential oil, a volatile compound, plays a role in herbicidal action on broadleaf weeds. Synthesis and technology nanoemulsion-based herbicide help protect the effectiveness of oils. The present study focused on the formulation, characteristics of clove essential oil-based nanoemulsion, and their herbicidal activity against Ruellia tuberosa L. The nanoemulsion containing clove essential oil was produced using the high-energy emulsification method with Tween 85 (HLB 11) and Span 85 (HLB 1.8) as an emulsifier agent (non-ionic surfactant), enabling the performance of clove oil nanoparticle size. The characteristic of nanoemulsion after being prepared 1 day showed that the droplet size, polydispersity index (PI) and zeta potential value was 152.5 nm, 0.162 and -32.68 mV, respectively. Even after 28 days, these characteristics have changed slightly. To confirm the droplet size, transmission electron microscope (TEM) images verified the clove oil-based nanoparticle size. Pre-emergence herbicidal activity under laboratory tests showed that the nanoemulsion at a concentration of 100, 200, 400 and 800 µL L-1 of oil reduced the germination and seedling growth of the tested weed. Inhibitory effect was absolutely at 800 µL L-1 of clove oil. Post-emergence application of nanoemulsion at a various concentration of 2000, 4000, 8000 and 10000 µL L-1 of oil was sprayed on 2-4 true leaves stage of tested weed. After foliar-applied nanoemulsion 24 h, the results showed that chlorophyll and carotenoid content decreased. Moreover, an increase in relative electrolyte leakage (REL) and malondialdehyde (MDA) indicated membrane disruption. This research supported that the clove oil-based nanoformulation may have a strong phytotoxic effect on R. tuberosa L. The nanoemulsion from clove oil is friendly to the environment and promote natural herbicide production for sustainable weed control.
Keywords: bioherbicide; herbicidal activity; natural product; stability; weed control